ANALISIS SEMIOTIK PADA IKLAN IPAD PRO - Purnama, Linda Cahya; Dewi, Putu Ary Sintya (Prosiding Seminar Nasional Bahasa Ibu, 2025)
The research focuses on advertisements for iPad Pro , one of the best-selling smart tablets in Indonesia. This research aims to observe the visual meanings and messages in iPad Pro advertisements. A qualitative approach and a qualitative descriptive method are used in the study. The data was taken from Apple's official website, and the images used as data were collected by screenshots and collected in Google Documents. Discourse analysis theory by Coulthard (1977) and semiotic theory by Émile Benveniste and Claude Lévi-Strauss were applied in the analysis process. The research found that the iPad Pro advertisement conveys to the public that technology can lead humans to a better life where humans work using modern technology, one of which is the iPad Pro.